Emerging low-dimensional materials for nanoelectromechanical systems resonators. Issue 1 (2nd January 2023) - Ban, Siyuan; Nie, Xuchen; Lei, Zhihao; Yi, Jiabao; Vinu, Ajayan; Bao, Yang; Liu, Yanpeng
Abstract : Low-dimensional materials (LDMs), due to exotic mechanical, optical and electrical properties enhanced by ultrahigh surface-to-volume ratio and quantum confinements, have taken centerstage in nanoelectromechanical system (NEMS) resonators. The ability to survive from high strains and complex environments enables LDMs-based NEMS resonators innovative effectuations for mass-, gas- and bio-sensings and computings. In this review, we highlighted the fabrication, actuation, detection, figure of merit, influence factors and recent process of LDMs-based NEMS resonators. After overviewing representative applications and feasible directions, we summarized the confronted challenges in fabrications, tunings and utilizations of LDMs-based NEMS resonators. Finally, the prospects that may properly tackle these obstacles were concluded, attempting to offer useful guidelines for both theoretical and experimental experts to promote NEMS resonators one step closer toward industrializations. IMPACT STATEMENT: This review delineates the principles and advances of nanoelectromechanical system resonators based on low-dimensional materials, followed by promising applications, such as sensings, nano-electronics and quantum detections.